ANALISA KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2000 PADA PT MARDOHAR CATUR TUNGGAL GAYAANALISA KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2000 PADA PT MARDOHAR CATUR TUNGGAL GAYA - Bintara, Rista; Nurlis, Nurlis (Teropong : Jurnal Manajemen dan Bisnis, 2020)
This research has a purpose to analyze the financial performance of PT Mardohar Catur Tunggal Gaya before the application of Quality Management System ISO 900I:2000 in the period of2005-2006, and after the implementation of Quality Management System ISO 9001:2000 in the period of2007-2008 by using financial ratio. In this research the data is used the year-end financial statements of PT Mardohar Catur Tunggal Gayafor in the period of2005-2008. This research uses descriptive quantitative method The results of this research shows that the financial performance of PT Mardohar Catur Tunggal Gaya is good enough where there is an increase in.financialperformance which is seen.from the better trend value ratio after the implementation of Quality Management System ISO 9001:2000. This proves that the Quality Management System ISO 9001:2000 has a role in supporting the financial performance of PT Mardohar Catur Tunggal Gaya.